2006
DOI: 10.1519/r-55551.1
|View full text |Cite
|
Sign up to set email alerts
|

Kinematical Analysis of the Snatch in Elite Male Junior Weightlifters of Different Weight Categories

Abstract: The purpose of this study was to analyze the differences in the technical pattern of the snatch in elite junior weightlifters of different weight categories. The sample was a group of 33 men weightlifters from different weight categories. The comparative study included 2 groups, taking into account weight categories. Group A included 17 weightlifters from the lightest categories, 56 and 62 kg; group B included 16 weightlifters from the heaviest categories, 85 and 105 kg. Three-dimensional photogrammetry techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 15 publications
2
45
0
2
Order By: Relevance
“…Results of previous studies do support the compressive and shear force and bending moment results seen for our spinal model. Kinematic analyses for barbell vertical velocity 25 and angular displacement 51 show the same patterns as our model with declines at the knee and ankle during transition from the first pull to the second pull, a peak at the second pull, and a rapid decline thereafter.…”
Section: Hang Clean and Hang Snatchsupporting
confidence: 71%
See 2 more Smart Citations
“…Results of previous studies do support the compressive and shear force and bending moment results seen for our spinal model. Kinematic analyses for barbell vertical velocity 25 and angular displacement 51 show the same patterns as our model with declines at the knee and ankle during transition from the first pull to the second pull, a peak at the second pull, and a rapid decline thereafter.…”
Section: Hang Clean and Hang Snatchsupporting
confidence: 71%
“…For example, Campos and co-workers reported no kinetic differences among the power clean, hang power clean and midthigh power clean in a sample of 16 collegiate female athletes, 25 but this was not the case in elite male rugby players, 19,20 indicating that spinal forces and moments may vary among these lifts. Additionally, Escamilla et al 13 reported significant biomechanical differences between the conventional and summon deadlifts, supporting the application of this model during these common variations.…”
Section: Hang Clean and Hang Snatchmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of research on the biomechanical aspects of weightlifting has been focused on the snatch exercise [72, 73, 76, 79, 81-91, 93-96, 98]. Some of this literature reports the use of three dimensional kinematics to track the bar bath and examine joint characteristics [76,84,90,95], while other literature reports investigations of the snatch technique of various populations [72, 73, 81-83, 85, 86, 88, 89, 96, 98]. The remaining weightlifting literature has discussed the technique of the clean and power clean [28,77,78,97], hang power clean [77,80], jerk [71], clean pull and snatch pull [63], hang high pull [61], jump shrug [60], and mid-thigh pull [62] as well as examined technique changes of the clean, power clean, and jerk [87,92,98].…”
Section: Previous Weightlifting Literaturementioning
confidence: 99%
“…Many of the recent studies have focused on the snatch and clean (Enoka, 1979;1983;1988;Garhammer, 1979;1980;1982;1991;Gourgoulis et al, 2002;Haff et al, 2003;Gourgoulis et al, 2004;Campos et al, 2006;Berning et al, 2008;Lauder and Lake, 2008) with comparatively little work done on the jerk, despite evidence that the majority of missed clean and jerks were due to errors in the jerk phase (Medvedev, Masalgin, Herrera, and Frolov, 1982;Grabe and Widule, 1988). While most weightlifters understand that the elasticity of the bar has a profound effect on the outcome of the lift, many of these studies assume the barbell is a completely rigid object.…”
Section: Introductionmentioning
confidence: 99%